SISTEM MONITORING SPEED SETTING PADA ROLLER MIXER BERBASIS MIKROKONTROLER ARDUINO UNO - Sijabat, Salomo; Andany, Arif (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Roller mixer is a laboratory tool that serves to mix blood samples and reagents.  In this case, the substances that are mixed are blood and anti-clotting agents (coagulants).  In the process of mixing the blood, the timer and the rotational value of the motor are set by the selector switch.  The design of the speed setting of the roller mixer tool is made so that the user can control and monitor how much the value of the motor speed used is displayed on the 16x2 LCD display. This research will be conducted at the Electronics Laboratory of Sari Mutiara University, Helvetia District, Medan City.  This type of research method is experimental research, namely conducting direct experiments.  The components in monitoring this tool are microcontroller, display, timer setting, speed setting and roller. After carrying out the research process on the design of this tool, the measurement results obtained from the Infrared Sensor are displayed on the LCD, with a minimum speed measurement of 36, Medium 38 and a maximum of 44 rpm.  With a comparison from a thacometer with an average value of Minimum 44 Medium 54 and maximum 56.